2013
DOI: 10.4269/ajtmh.12-0023
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Viremia and Concentration of Circulating Nonstructural Protein 1 in Patients Infected with Dengue Virus in Mexico

Abstract: Abstract. Higher levels of viremia and circulating nonstructural protein 1 (NS1) have been associated with dengue disease severity. In this study, viremia and circulating NS1 levels were determined in 225 serum samples collected from patients in Mexico infected with dengue virus serotypes 1 and 2 (DENV-1 and DENV-2). Patients with dengue hemorrhagic fever (DHF) who were infected with DENV-1 showed higher levels of circulating NS1 than patients with dengue fever (DF) (P = 0.0175). Moreover, NS1 levels were high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 36 publications
5
64
1
Order By: Relevance
“…A previous study also observed that there was no evidence of positive selection in the structural proteins of DENV-2 including the NS1 protein [29]. This indicates that NS1 needs to retain its structure and amino acid sequences to be able to perform its function effectively.…”
Section: Discussionmentioning
confidence: 91%
“…A previous study also observed that there was no evidence of positive selection in the structural proteins of DENV-2 including the NS1 protein [29]. This indicates that NS1 needs to retain its structure and amino acid sequences to be able to perform its function effectively.…”
Section: Discussionmentioning
confidence: 91%
“…We first validated our assay and demonstrated dose-response curves in buffer ( Figure 3) for each dengue serotype. We could demonstrate a lower limit of detection (LoD) of 0.5 ng/mL (DENV-1), 0.2 ng/mL (DENV-2), 0.8 ng/mL (DENV-3) and 1 ng/mL (DENV-4), well below reported levels of circulating NS1 in patients affected from primary or secondary infection (reference values of circulating NS1: 13 ng/mL -1880 ng/mL for patients infected with DENV-1 and 4 ng/mL -266 ng/mL for patients infected with DENV-2 in a cohort study of 225 patients) 37 . We were able to demonstrate sensitive and selective detection of each dengue serotype with minimal cross talk between serotypes.…”
mentioning
confidence: 85%
“…In some cases, it has been described that there is no association between viremia and NS1 levels in severe clinical condition [78,79]. In addition, the infected serotype might have a role in diagnosis sensitivity; it has been reported that NS1 levels are higher in patients infected with DENV1 than with DENV2 [76,78].…”
Section: Differential Diagnosismentioning
confidence: 98%
“…Although it has been described that the highest levels of viremia and NS1 are observed in the first 2-3 days after fever onset, it is well defined that both parameters are higher in patients with secondary DENV infections and the severe form of dengue [39,[73][74][75][76][77]. In some cases, it has been described that there is no association between viremia and NS1 levels in severe clinical condition [78,79]. In addition, the infected serotype might have a role in diagnosis sensitivity; it has been reported that NS1 levels are higher in patients infected with DENV1 than with DENV2 [76,78].…”
Section: Differential Diagnosismentioning
confidence: 98%
See 1 more Smart Citation